TEACHING UNIVERSITY STUDENTS IN A FOREIGN LANGUAGE IN MODERN CONDITIONS: TRADITION AND INNOVATION - Mahametova , Dilnavoz Botirovna (Innovative Development in Educational Activities, 2024)
This thesis looks at how foreign language instruction is changing for University students in contemporary classrooms and examining the evolving landscape of teaching within modern educational settings. The study explores the relationship between innovative approaches and standard pedagogies and how it affects language learning and academic advancement. With an emphasis on communicative approaches, immersive experiences, technological integration, and the role of educators, this research attempts to give higher education institutions a thorough grasp of modern, efficient language teaching methods.